Multicentric Carpo-Tarsal Osteolysis. Issue 1 (2nd February 2023) - Tannouri, Lea; Simoni, Paolo
MCTO is a rare autosomal-dominant inherited disorder that causes bone destruction and deformity of the appendicular bones in children, with the carpal and tarsal bones severely affected. Imaging can narrow the differential diagnosis between MTCO and other diseases that cause osteolysis of the joints in children. The MCTO diagnosis is confirmed by a mutation of the MAFB gene. Teaching Point: Multicentric carpo-tarsal osteolysis (MTCO) in childhood must be considered in the differential diagnosis of severe osteolysis on radiographs.